The effect of carbohydrate and marine peptide hydrolysate co-ingestion on endurance exercise metabolism and performance - Siegler, Jason C (BioMed Central, 2013)
BACKGROUND: The purpose of this study was to examine the efficacy of introducing a fish protein hydrolysate (PEP) concurrently with carbohydrate (CHO) and whey protein (PRO) on endurance exercise metabolism and performance. METHODS: In a randomised, double blind crossover design, 12 male volunteers completed an initial familiarisation followed by three experimental trials. The trials consisted of a 90 min cycle task corresponding to 50% of predetermined maximum power output, followed by a 5 km time trial (TT). At 15 min intervals during the 90 min cycle task, participants consumed 180 ml of CHO (67 g(.)hr(-1) of maltodextrin), CHO-PRO (53.1 g(.)hr of CHO, 13.6 g(.)hr(-1) of whey protein) or CHO-PRO-PEP (53.1 g(.)hr(-1) of CHO, 11 g(.)hr(-1) of whey protein and 2.4 g(.)hr(-1)of hydrolyzed marine peptides). RESULTS AND CONCLUSIONS: During the 90 min cycle task, the respiratory exchange ratio (RER) in the CHO-PRO condition was significantly higher than CHO (p < 0.001) and CHO-PRO-PEP (p < 0.001). Additionally, mean heart rate for the CHO condition was significantly lower than that for CHO-PRO (p = 0.021). Time-to-complete the 5 km TT was not significantly different between conditions (m ± SD: 456 ± 16, 456 ± 18 and 455 ± 21 sec for CHO, CHO-PRO and CHO-PRO-PEP respectively, p = 0.98). Although the addition of hydrolyzed marine peptides appeared to influence metabolism during endurance exercise in the current study, it did not provide an ergogenic benefit as assessed by 5 km TT performance.